2019
DOI: 10.1016/j.abrep.2019.100201
|View full text |Cite
|
Sign up to set email alerts
|

Leisure activity and alcohol use among Ukrainian adolescents

Abstract: The aim of this paper was to investigate associations between engagement in various types of leisure activity and alcohol use among Ukrainian adolescents. We conducted a cross-sectional survey of 1075 adolescents who were enrolled in the Family and Children of Ukraine birth cohort study using a self-administered questionnaire to determine how they prefer to spend their leisure time and their use of alcohol. Use of social media was associated with a higher risk of ever having used alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, to cope with and protect against chronic diseases such as cancer, addiction, and obesity, it is recommended to increase happiness and satisfaction by planned leisure time. 8,10,11 The World Health Organization has defined that the life quality is the perception of the people in the whole of their culture and value judgments in terms of goals, expectations, and standards. 12 In other words; a person's perception of his or hers own health as a sociocultural environment is called life quality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to cope with and protect against chronic diseases such as cancer, addiction, and obesity, it is recommended to increase happiness and satisfaction by planned leisure time. 8,10,11 The World Health Organization has defined that the life quality is the perception of the people in the whole of their culture and value judgments in terms of goals, expectations, and standards. 12 In other words; a person's perception of his or hers own health as a sociocultural environment is called life quality.…”
mentioning
confidence: 99%
“…3,6,14 Thus, the life quality and life satisfaction of the individual may be increased. 4,5,10,15,16 Life satisfaction refers to how much the individual enjoys the life they live. 17 There are many variables that affect life satisfaction.…”
mentioning
confidence: 99%
“…The choice of leisure activity is important to adolescent development and to life satisfaction. Tourism is the least popular leisure time activity among Ukrainian adolescents in Kamianske, Ukraine (Hryhorczuk et al, 2019). Understanding the predictors of tourism behavior in this population can facilitate the development of tourism in Ukraine and offer adolescents greater opportunities to pursue tourism leisure time activities that expand knowledge, promote social development, improve cultural awareness, promote health and well-being and contribute to overall life satisfaction.…”
Section: Previousmentioning
confidence: 99%
“…(Akhmedova, 2017). Hryhorczuk et al (2019) observed that among adolescents in Kamianske, tourism is the least popular way for them to spend their leisure time. Despite these obstacles the World Council of Tourism and Travel predicts that the tourist market of Ukraine is going to flourish during the next 10 years (Akhmedova, 2017).…”
Section: Introductionmentioning
confidence: 99%